Handbook of special education - Kauffman, James M.; Hallahan, Daniel P., 1944- (Routledge, 2011)
Special education is now an established part of public education in the United States--by law and by custom. However, it is still widely misunderstood and continues to be dogged by controversies related to such things as categorization, grouping, assessment, placement, funding, instruction, and a variety of legal issues. The purpose of this 13-part, 57-chapter handbook is to help profile and bring greater clarity to this sprawling and growing field. To ensure consistency across the volume, chapter authors review and integrate existing research, identifying strengths and weaknesses, note gaps in the literature, and discuss implications for practice and future research. This book is an appropriate reference volume for anyone (researchers, scholars, graduate students, practitioners, policy makers, and parents) interested in the state of special education today: its research base, current issues and practices, and future trends. It is also appropriate as a textbook for graduate level courses in special eduction.